Prediction of evanescent coupling efficiency in two parallel silica nanowires. (1st August 2019) - Sheu, Tony W.H.; Kao, C.Y.; Chang, Y.W.; Li, J.H.
Abstract: In this study the efficiency of evanescent wave coupling between two air-clad silica nanowires in single-mode operation is numerically predicted in time-domain using the finite difference method. To this end, a three-dimensional scheme developed for solving the Maxwell's equations on staggered grids will be employed. The electric and magnetic field solutions are sought subjected to the zero-divergence condition (or Gauss's law) in discrete level. In addition, we aim to conserve Hamiltonians existing in ideal Maxwell's equations at all times by adopting the explicit second-order accurate symplectic partitioned Runge–Kutta temporal scheme. Moreover, all the spatial derivative terms in the Faraday's and Ampère's equations are approximated by the proposed scheme which can render not only fourth-order spatial accuracy, but also minimize the discrepancy between the exact and the derived numerical phase velocities.